The Improvement of Students’ Learning Outcomes and Report Writing Skills at The Sixth Grade Elementary School Use the Learning Model Think-Talk-Write and Wordwall Media (Universitas Negeri Semarang, 2022)
The implementation of Indonesian Class VI learning, especially in writing student reports, has various obstacles. This is based on several factors including students who do not understand the form of the report to be written, students have difficulty in starting and determining the contents of the report to be written. This research is quantitative research, that is Quasi Experimental or often referred to as quasi-experimental aims to improve student learning outcomes and report writing skills with the Think Talk Write learning model assisted by Wordwall media. Determination of the sample using purposive sampling technique, purposive sampling is a sampling technique with certain considerations. Located at SDN 02 Sukorejo and SDN 01 Botekan in Ulujami District, Pemalang Regency. The sample of this study amounted to 56 students of class VI Elementary School. Data was collected through test, observation, interview, and documentation techniques. Data analysis techniques with validity, reliability, level of difficulty, normality test, homogeneity test, one sample t-test, two sample t-test, N-gain test, and simple correlation test. Based on the results of simple regression, it is known that (p = 0.00) < (? = 0.05); This means that students' activities in using think talk write learning assisted by Wordwall media affect students' writing skills and increase student learning outcomes as indicated by the results of the sig (2-tailed) regression test of 0.00 < 0.05; it means that students' writing skills affect student learning outcomes.